Comment on "Migration-assisted, moisture gradient process for ultrafast, continuous CO2 capture from dilute sources at ambient conditions" by A. Prajapati, R. Sartape, T. Rojas, N. K. Dandu, P. Dhakal, A. S. Thorat, J. Xie, I. Bessa, M. T. Galante, M. H. S. Andrade, R. T. Somich, M. V. Rebouças, G. T. Hutras, N. Diniz, A. T. Ngo, J. Shah and M. R. Singh, Energy Environ. Sci., 2022, 15, 680. Issue 9 (8th August 2022) - Casado, Juan
Abstract : The title study lacks practical feasibility since it mostly ignores O2 released with CO2 ; underestimates the impact of vapour, SOx, and NOx on the system; anodes are unstable vs O2 evolution, and the total voltage does not match the quoted voltage. Abstract : R&D efforts on carbon capture and storage (CCS) are gaining unprecedented momentum in the context of the current climate crisis. A growing body of work is proposing new methods to extract this greenhouse gas from flue gases or directly from the air. The title paper, published in this Journal, describes one electrochemically driven process to capture and separate CO2 from dilute sources by establishing a water gradient across an anion exchange membrane (AEM) that separates the organic solvent and an aqueous solution. The organic medium is ethylene glycol saturated with KOH, which captures CO2 and produces a high concentration of HCO3 − which migrates to the aqueous side, where bicarbonate is converted back to CO2 . Here we comment on this new process and provide several reasons we consider that, although interesting from an academic point of view, it lacks practical feasibility on an industrial scale. We also point out some inconsistencies in the article.